Risk factors for the first episode of Acinetobacter baumannii resistant to colistin infection and outcome in critically ill patients - Mantzarlis, Konstantinos (J Med Microbiol, 2020)
INTRODUCTION: To identify risk factors for the first episode of Acinetobacter baumannii resistant to colistin (ABCR) infection in critically ill patients. AIM: Prospective observational study. METHODOLOGY: ICU patients who required mechanical ventilation for >48 h during a 36 month period. Clinical and microbiological data were studied; characteristics of patients infected with ABCR were compared with those of critically ill patients who presented infection due to A. baumannii sensitive to colistin (ABCS). RESULTS: Twenty patients presented with ABCR infection, and 57 patients ABCS infection. Compared to patients with ABCS infection, patients suffering from ABCR infection had received more frequent and/or for longer duration dosing of several antibiotics active against Gram-negative bacteria (P<.05). Moreover, the duration of mechanical ventilation, and the presence of invasive procedures and tracheostomy prior to infection were associated with ABCR infections. The duration of carbapenem administration was an independent risk factor for ABCR infection [odds ratio (OR), 1.21; 95 % confidence interval (95 %, CI), 1.00 to 1.45; P=.049]. Mortality rate for patients with ABCR infection was higher (85 vs 39 % for the ABCS group). Sequential organ failure assessment score on admission, Charlson score and ABCR infection were independent risk factors for mortality. CONCLUSION: ABCR infection is a life-threatening infection, which might be more common in patients with previous use of antibiotics, especially carbapenems.